Epidemiology of childhood manifest strabismus in the Republic of Moldova. (2nd July 2020) - Paduca, Ala; Arnaut, Oleg; Cardaniuc, Corina; Spinei, Larisa; Bendelic, Eugeniu; Bruenech, Jan Richard; Lundmark, per Olof
ABSTRACT: The purpose of this study was to determine the prevalence and the rate of newly detected pediatric manifest strabismus cases in the Republic of Moldova. A descriptive study was conducted in the Republic of Moldova. The data about the number of children that passed the prophylactic ophthalmological examination every year (children of 3 months– 17 years), the number of new strabismus cases found annually and the number of manifest strabismus cases under evidence were collected from the Health Family Centers in the Northern, Southern, and Central districts of the Republic of Moldova. The study period was performed in 2011– 2017. The prevalence rate of pediatric manifest strabismus in the study was 1.3%. The rate of newly diagnosed strabismus was 0.2%, with a higher ratio for esotropia versus exotropia (16.7/4.9 cases per 10000 children). The age of esotropia detection was mainly in the ﬁrst 6 years of life (76.1%); beyond this age, exotropia predominates until the teenage years (75.6%). The study revealed a lower prevalence of pediatric manifest strabismus in comparison with the prevalence reported in other European countries. Esotropia was the most common type among patients with strabismus, this being detected mainly at ﬁrst 6 years of life. The prevalence rate of exotropia was lower and the detection age was more frequent beyond the age of 6 years. The age at which most pediatric manifest strabismus cases were detected ranged between 3 and 6 years.